MYTHOLOGICAL CHARACTERS REPRESENTING THE UNITED STATES ENVIRONMENTAL ISSUES IN RICK RIORDAN’S PERCY JACKSON AND THE OLYMPIANS SERIES - ALHIMNI, LOVE FISTIANA MARCH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Greek Mythology, mythological character, environmental issues, AmericaMyth is a story that is produced in ancient time and represented the philosophy of life. Myth usually contains some earlier stories to explain natural phenomena that cannot be explained by human at that time. The collections of myth are called mythology. One of the famous mythologies in this world is Greek Mythology and the important part of Greek Mythology is the story of Gods and Goddesses. God or Goddess character is representation of natural life and it is represented interestingly in the novel written by Rick Riordan entitled PercyJackson and the Olympians Series. The representation of nature, especially which is related to environmental issues, becomes an interesting topic in in this novel. Due to this, understanding further about representation of environmental issues in America through the existence of mythical characters in this novel is significant to be done.Qualitative research is used in this research because it concerns with the description of condition of nature in America nowadays. Therefore, qualitative design is needed. Mythological study is used to help the researcher understands more about mythological characters and theirs functions within the realm of preserving natural sources. Ecocriticism is also used to analyze the environmental degradation which happens in America as portrayed in Riordan’s novels.The result of the study shows that some mythological characters symbolizeenvironmental issues in America, particularly about the degradation condition and the effort of make them better. They are Poseidon, Pan, and Satyrs. Poseidon is the a mythical character representing of water condition. The function of Poseidon here is to repair the condition of polluted water in America. Pan is the mythical character representing wild area or forest. His condition pictures the decreasing certain number of forest area in America. And the last character is Satyr who represents the environmentalist movement in America.The researcher suggests the next researchers who want to conduct similar research to have a better knowledge in analyzing this topic and look for other interesting mythical characters with different point of view. Furthermore, the next researchers can investigate also the psychological condition of mythical figures using psychological theories, since the existence of mythical characters imply psychological condition undergone by human beings.